Partai Komunis Indonesia dalam Persaingan Menuju Pemilu DPRD 1957 di Jawa Timur - Eriyano Wempy Gilarsi (Departemen Politik dan Pemerintahan, Universitas Gadjah Mada, 2023)
This research discusses the preparation of the Indonesian Communist Party (PKI) ahead of the election for members of the Regional Parliament (DPRD) in East Java in 1957. The DPRD resulting from the election (pemilu) needed to be formed immediately to then be tasked with electing a Regional Head. Apart from already being on the government's agenda, this elections was intended to meet the demands for regional autonomy which had become increasingly intense in the late 1950s. East Java became one of the areas where this election was held and the PKI became one of the most ambitious contestants to win it. By using historical methods through a political history approach, the authors analyze the efforts made by the PKI in welcoming the DPRD elections in East Java. The data used in this study came from archives and newspapers published in the 1950s, books, journals and dissertations. In addition to appearing as a party that carries the ideals of national unity to approach the masses, the PKI's efforts to collect election funds appear to be more organized. Even though it was confronted with a state of martial law and the imitation of pictures by other parties, the PKI was able to face it tenaciously.